A PROPOSAL FORECASTING MODEL FOR THE GROWTH OF THE MOBILE TELEPHONE MARKET IN BRAZIL - Guedes, Luís Fernando Ascenção; Vasconcellos, Liliana (Future Studies Research Journal: Trends and Strategies, 2009)
The element that characterizes the information era is the key role of communication and connectivity, broadly speaking, in social life. Among the ways in which users can enter voice or data networks, one of the most prominent is mobile telephony. Therefore, determining the number of mobile phones in operation in Brazil over the next few years is a relevant issue for the strategic planning of firms in this sector. Thus, this article aims to define a mathematical model suitable for calculating the number of mobile phones in operation in Brazil in forthcoming years, as a function of the behavior of the following variables during the course of time: GDP per capita, population and percentage GDP growth. To this end, a quantitative study was conducted, based on secondary data taken from preceding survey; then a linear and polynomial regression was employed to correlate GDP per capita with mobile phone density. The results showed high correlation (97.5%) between phone density and Brazil’s GDP growth from 2004 to 2007. This correlation is also high in Russia, India and China. Moreover, we found that the limiting value of good correlation between GDP per capita and mobile phone density is roughly US20,000.00 and that the limit of mobile telephony penetration is approximately 120%. Thus, taking into account several economic growth rates, we estimate that the penetration of mobile telephony will take 5 to 11 years to reach its upper limit in Brazil. Key words: Mobile telephony. Prediction model. Telecommunications.